(untitled) (Research, Society and Development, 2020)
This work’s purpose is to evaluate the use of the golden mussel shell (Limnoperna fortunei) as a limestone’s substitute in soil correction. For this, 30 L pots were filled with acidic and sandy soil, to which were added doses (0, 1.0; 2.0 and 2.5 t ha-1) of milled mussel shells-MM (0, 25mm), mussel shells in pieces-MP (8 mm) and limestone-CALC, the latter as a reference. A fertilization with NPK (08-28-16) of 1t ha-1 was carried out for the initial growth of corn, the indicator plant. After 30 days of soil incubation with the correctives (CALC, MM and MP), the corn was sown and remained in cultivation for 90 days. After this period, the soil (fertility) and plant (height, stem diameter, leaf chlorophyll, dry mass of aerial part and root and root length) evaluations were carried out. The results show that MM can replace CALC, since it increases the Ca2+ in the soil, the pH, reduces Al3+ and potential acidity, a behavior statistically equal to CALC. The MP produced the same response pattern for the variables analyzed; however, it requires larger doses or more time for reaction, due to the coarser particle size. Based in the observations, it is concluded that MM can replace CALC and the aluminum neutralization occurs for both, with 1.8 t ha-1, while for MP 3.05 t ha-1 is required. Corn also responded to CALC, MM and MP, so the use of the mussel shell as a corrective can be an effective mean of disposing this residue.